1998
DOI: 10.1097/00005392-199812010-00089
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Ischemia-Induced Cavernosal Smooth Muscle Relaxation Impairment in a Rabbit Model of Vasculogenic Erectile Dysfunction

Abstract: Impairment of endothelium-dependent relaxation by Hch occurs secondary to disruption of the NO formation in cavernosal endothelium. Improvement of endothelium-dependent relaxation by L-arginine may suggest lack of availability of L-arginine in cavernosal tissue from the Hch animals. Impairment of endothelium-dependent and neurogenic relaxation by CCI occurs secondary to disruption of the NO formation due to an alteration in the expression or activity of NOS and increased output of constrictor eicosanoids in ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 16 publications
0
74
1
1
Order By: Relevance
“…The mechanism of hypercholesterolemia induced dysfunction of the corporal endothelium may be due to impaired ability of the endothelium to synthesize NO 24 or decreased synthesis or availability of L-arginine. 25 Some authors reported the negative impact of hypercholesterolemia on penile hemodynamics. 19 In the current study, no statistically significant relationship between cholesterol level In contrast with the findings of some authors who reported no correlation between CsA and erectile function 9,19 we found statistically higher incidence of ED among RTR receiving CsA-based immunosuppressive regimens.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of hypercholesterolemia induced dysfunction of the corporal endothelium may be due to impaired ability of the endothelium to synthesize NO 24 or decreased synthesis or availability of L-arginine. 25 Some authors reported the negative impact of hypercholesterolemia on penile hemodynamics. 19 In the current study, no statistically significant relationship between cholesterol level In contrast with the findings of some authors who reported no correlation between CsA and erectile function 9,19 we found statistically higher incidence of ED among RTR receiving CsA-based immunosuppressive regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Whether this reflects a reduction of A 2B receptor binding sites or results from impairment of distal effectors pathways needs further investigation. Dysfunctional blood vessels can alter the balance between relaxant and constrictor actions of endogenous prostanoids (Azadzoi et al, 1998;Behr-Roussel et al, 2003). This, together with the reduced NO-mediated component, might explain the difficulty in relaxing HCC strips from vasculogenic ED patients in response to NECA and ACh.…”
Section: Downloaded Frommentioning
confidence: 99%
“…The animal model of arteriogenic ED was developed as previously described. 4,17 Briefly, the CI group underwent bilateral balloon endothelial cell injury of the iliac arteries, received a 0.5% cholesterol diet for 4 weeks, and then a regular diet. Animals were studied at 4, 6, 8, and 16 weeks after the balloon arterial injury.…”
Section: Animal Model Of Arteriogenic Edmentioning
confidence: 99%